A case of an intramural, cavitated feline gastrointestinal eosinophilic sclerosing fibroplasia of the cranial abdomen in a domestic longhair cat - Gordon A Davidson; Samantha S Taylor; Melanie J Dobromylskyj; Francesco Gemignani; Helen Renfrew (Journal of Feline Medicine and Surgery Open Reports, 2021)
Case summary A 5-year-old neutered male domestic longhair cat was presented for the investigation of a cranial abdominal mass following a 1-month history of inappetence and lethargy. Abdominal ultrasound revealed a large cavitated mass confluent with the mesenteric aspect of the descending duodenum. At surgery, the mass was found to involve the pylorus, proximal duodenum and pancreas, and was non-resectable. Histopathological examination of surgical biopsies revealed a non-neoplastic process involving eosinophils and fibroplasia. Relevance and novel information This case report describes an uncommon feline gastrointestinal pathology with an unusual appearance that may provide an additional differential diagnosis other than neoplasia or abdominal abscess when confronted with a cavitated abdominal mass in cats.